THE SYSTEMATIC SIGNIFICANCE OF LEAF EPIDERMAL MICROMORPHOLOGY OF TEN NEPENTHES SPECIES (NEPENTHACEAE) FROM PENINSULAR MALAYSIA - Mohd Norfaizal Ghazalli; Amin Asyraf Tamizi; Muhamad Ikhwanuddin Mat Esa; Edward Entalai Besi; Dome Nikong; Anuar Rasyidi Mohd Nordin; Ahmad Zaki Zaini (BRIN Publishing (Penerbit BRIN), 2019)
GHAZALLI, M. N., TAMIZI, A. A., ESA, M. I. M., BESI, E. E., NIKONG, D., NORDIN, A. R. M. & ZAINI, A. Z. 2019. The systematic significance of leaf epidermal micromorphology of ten Nepenthes species (Nepenthaceae) from Peninsular Malaysia. Reinwardtia 18(2): 81−96. — The pitcher plants of Malaysia belong to the genus Nepenthes and can be found thriving in swampy areas, along the roadside, on hillslopes and in mountainous terrains depending on species and their ecological preferences. In this study, cuticle micromorphology of ten species of Nepenthes (Nepenthaceae) collected from Peninsular Malaysia was intensively studied through scanning electron microscopy (SEM) to characterise and investigate diagnostic characters of cuticle micromorphology that can be useful in Nepenthes classification. A total of eleven characters from the inner and outer cuticles were enumerated in details and these characters have a value either for infrageneric classification or for diagnostic identification of the species. Characters observed and analysed were related to the epidermal cells, subsidiary cells, stomatal complex i.e type of waxes on both epidermal surfaces, abaxial and adaxial cuticular ornamentation, stomata characteristics, stomata formation, stomata frequency, cuticular ornamentation on stomata, shape of the stomata, stomata size, trichome existence and type of trichomes. Nepenthes ampullaria is clearly distinguished from the other species by markedly different types of tufted and multicellular trichomes of the epidermal cells on both leaf epidermal surfaces. For N. alba, its cuticular feature showed groovy cuticular pattern on the abaxial and adaxial surface, hence, can serve as a diagnostic cuticular pattern for this species. From these findings, the species delimitation based on cuticular features show a clear resolution, however some species might be individually distinct based on the combination of characters examined.